Water conservation behavior and environmental concerns: Evidence from a representative sample of Italian individuals. (15th August 2017) - Aprile, Maria Carmela; Fiorillo, Damiano
Abstract: Water conservation represents important pro-environmental behavior for a sustainable environment. We investigate the link between water conservation behavior and general environmental concerns, using a large dataset from the Multipurpose Household Survey conducted annually by the Italian Central Statistics Office and controlling for socio-economic characteristics and regional variables. Univariate probit models show that pollution and resource exhaustion are positively related to individual water conservation behavior while alteration of environmental heritage exhibits a negative relationship with water saving behavior. Our findings are robust to the inclusion of environment knowledge and social capital variables. Robustness analysis also indicates that television and radio, participation in environmental initiatives, money for environmental protection and churchgoing are significant positive drivers of water conservation behavior, as are several individual characteristics like having young children, being older, poorly educated, a homeowner, unemployed and retired. Highlights: We study the link between water conservation behavior and environmental concerns. We use an Italian representative dataset and univariate probit models. Water conservation behavior is linked to egoistic, altruistic and biospheric concerns. The results are robust to knowledge and social capital variables. Environmental knowledge is a driver of water conservation behavior.